History of ancient India standard six - Shinde, Bapusaheb; Joshi, Bharati; Prabhudesai, Sharad (Maharashtra State Bureau of Textbook Production and Curriculum Research, 2007)
Preface: "The "Primary Education Curriculum-2004" was prepared in the State of Mahrashtra following the "National Curricular Framework-2000". This syllabus is being implemented serially form the academic year 2006-2007. The syllabus includes History and Civics Std III onwards. The subject "Civics" was included in the History textbook up to Std V. The textbook of "Civics and Administration" is prepared separately, Std VI onwards."